Memorial: CARMAN GEORGE BLOUGH 1895-1981. - Moonitz, Maurice (The Accounting Review, 1982)
Presents an obituary for Carman George Blough, chief accountant of the U.S. authority Security and Exchange Commission, who died on March 9, 1981.